2010
DOI: 10.1007/s10681-010-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and physicochemical variation in Turkish kabuli chickpea (Cicer arietinum L.) landraces

Abstract: We examined the physical, physicochemical, and cooking properties of 91 kabuli chickpea landraces from Turkey, using two cultivars ( _ Inci and _ Izmir-92) as controls. All landraces were grown under the same agroclimatic conditions to eliminate variance caused by genotype 9 environment interactions. There was high diversity among the landraces in the contents of protein (17.55-23.31%), fat (4.45-6.11%), ash (2.54-3.41%), fiber (2.03-4.18%), starch (41.76-49.07%), moisture (6.39-10.57%), 100-seed weight (25.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
8
41
2
Order By: Relevance
“…Total phenols were found to be negatively and significantly correlated with seed weight, hydration capacity, swelling index, seed density and bound fructose of raffinose series oligosaccharides. Ozer et al, (2010) also reported significant positive correlation between seed weight, hydration capacity, swelling capacity and swelling index It was observed that tolerant genotypes had lower total phenol content and higher bound fructose of raffinose series oligosaccharides. Bound fructose of raffinose series oligosaccharides were significantly positively correlated with swelling index and swelling capacity.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Total phenols were found to be negatively and significantly correlated with seed weight, hydration capacity, swelling index, seed density and bound fructose of raffinose series oligosaccharides. Ozer et al, (2010) also reported significant positive correlation between seed weight, hydration capacity, swelling capacity and swelling index It was observed that tolerant genotypes had lower total phenol content and higher bound fructose of raffinose series oligosaccharides. Bound fructose of raffinose series oligosaccharides were significantly positively correlated with swelling index and swelling capacity.…”
Section: Resultsmentioning
confidence: 85%
“…So, they might be better as compared to the susceptible genotypes in terms of cooking quality. Ozer et al, (2010) also observed that physical properties of chickpea such as seed weight, seed density, moisture content and ash content can influence cooking quality.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In spite of the availability of rich genetic resources and the heavy consumption of legumes, including faba bean, in the Turkish diet, legume breeding in Turkey and other countries falls far behind cereals and other industrial crops (Baloch et al, 2010;Özer et al, 2011;Karaköy et al, 2012;Özer et al, 2012). The yield and the quality of cereals, soybean, cotton, and other crops in Turkey have shown tremendous improvements due to breeding activities.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to subfamily Papilionaceae of the family Leguminaceae. It's seeds contain 16.4-31.2% protein, 3.0% fibre, 38.1-73.3% carbohydrates, 1.6-9.0% cellulose, 0.2% Ca, 0.3% P, 3.0% ash, vitamins (C and B) and minerals (Mg, Zn, K, Fe) (Huda et al, 2003 andOzer et al, 2010). Combined inoculation of Rhizobium with Pseudomonas striata or Bacillus polymyxa and with Bacillus megaterium have shown increased dry matter, grain yield and phosphorus uptake significantly over the uninoculated control in legumes (Elkoca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%